2020
DOI: 10.26719/2020.26.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Smoking behaviour after enforcement of a 100% tax on tobacco products in Saudi Arabia: a cross-sectional study

Abstract: Background: Raising the prices of cigarettes is a common intervention to control tobacco use. In June 2017, Saudi Arabia imposed a 100% excise tax on tobacco products and energy drinks. Aims: This study aimed to evaluate the impact of the increase in prices on tobacco products and the resulting cigarette smoking behaviour in Jeddah, Saudi Arabia before and after the increase in tobacco product prices. Methods: This cross-sectional study was conducted between December 2017 and March 2018 in Saudi Arabian smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(24 reference statements)
4
9
0
Order By: Relevance
“…In 2017, the Saudi government levied excise taxes on tobacco products, which was reviewed in 2019 [ 12 ]. In addition, smoking in public places and the sale of cigarettes to minors are prohibited to control smoking [ 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, the Saudi government levied excise taxes on tobacco products, which was reviewed in 2019 [ 12 ]. In addition, smoking in public places and the sale of cigarettes to minors are prohibited to control smoking [ 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, currently, smoking in public places and sales to minors are prohibited [ 2 ]. Additionally, for the first time, the country implemented the WHO FCTC Article 6 by introducing an excise tax on tobacco products in 2017, which was revised in 2019 [ 12 ]. The KSA is also the pioneer of the “sin tax” in the Gulf region [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking prevalence in Saudi Arabia has a median of 16.5% among students, 22.6% among adults, and 25% among the those above 65 years of age [ 42 ]. However, our cohort showed a much lower rate of only 4.4%, these differences may be due to the cited study being conducted more than a decade ago, since then, in 2017, a 100% excise tax on tobacco products was enforced which led to a significant reduction in smoking in the country [ 43 ]. A meta-analysis of 19 studies showed a progression of COVID-19 in patients with a history of smoking (OR 1.91) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SFDA alone, being the main player in this case from the government side, has one million followers on its Arabic twitter account. It is worth mentioning that in 2019, 56% of internet users in Saudi Arabia were Twitter users, of which 71% were males averaging 26 years of age [24,28,71].…”
Section: Discussionmentioning
confidence: 99%
“…In June 2017, a 100% taxation was imposed on tobacco products in Saudi Arabia with an increase in standard product price [27]. No population-level studies have measured the effect of taxation on smoking in Saudi Arabia; however, the only study done in the city of Jeddah shows that almost 40% of respondents were resistant to smoking cessation despite the taxation, and 29% changed to a cheaper brand [28].…”
Section: Introductionmentioning
confidence: 99%